Investigating the poor outcomes of BRAF-mutant advanced colorectal cancer: analysis from 2530 patients in randomised clinical trials - Seligmann, JF; Fisher, D; Smith, CG; Richman, SD; Elliott, F; Brown, S; Adams, R; Maughan, T; Quirke, P; Cheadle, J; Seymour, M; Middleton, G (Oxford University Press, 2016)
To improve strategies for the treatment of BRAF-mutant advanced colorectal cancer (aCRC) patients, we examined individual data from patients treated with chemotherapy alone in three randomised trials to identify points on the treatment pathway where outcomes differ from BRAF wild-types.2530 aCRC patients were assessed from three randomised trials. End-points were progression-free survival, response rate, disease control rate, post-progression survival (P-PS) and overall survival. Treatments included first-line oxaliplatin/fluorouracil (OxFU) and second-line irinotecan. Clinicians were unaware of BRAF-status.231 patients (9.1%) had BRAF-mutant tumours. BRAF-mutation conferred significantly worse survival independent of associated clinicopathological factors known to be prognostic. Compared with wild-type, BRAF-mutant patients treated with first-line OxFU had similar DCR (59.2% versus 72%; adjusted OR = 0.76, P = 0.24) and PFS (5.7 versus 6.3 months; adjusted HR = 1.14, P = 0.26). Following progression on first-line chemotherapy, BRAF-mutant patients had a markedly shorter P-PS (4.2 versus 9.2 months, adjusted HR = 1.69, P < 0.001). Fewer BRAF-mutant patients received second-line treatment (33% versus 51%, P < 0.001), but BRAF-mutation was not associated with inferior second-line outcomes (RR adjusted OR = 0.56, P = 0.45; PFS adjusted HR = 1.01, P = 0.93). Significant clinical heterogeneity within the BRAF-mutant population was observed: a proportion (24.3%) had good first-line PFS and P-PS (both >6 months; OS = 24.0 months); however, 36.5% progressed rapidly through first-line chemotherapy and thereafter, with OS = 4.7 months.BRAF-mutant aCRC confers a markedly worse prognosis independent of associated clinicopathological features. Chemotherapy provides meaningful improvements in outcome throughout treatment lines. Post-progression survival is markedly worse and vigilance is required to ensure appropriate delivery of treatment after first-line progression.